Lost in Reintegration? - Magdalena Grenda (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article describes different approaches to the issue of image reintegration and filling in the areas of loss in photographs and photographic postcards. The approach varies depending on the context of the photographs’ usage, the owner’s expectations and the will of the photographer. The paper discusses treatments of various photographic artifacts and presents the complexity of conservation problems associated with photographic objects.  The diversity of solutions and decisions proves that there are numerous factors to consider and that there are no simple answers when it comes to decision making.